A teaching assistant's guide to child development and psychology in the classroom - Bentham, Susan (New York : Routledge, 2011)
Written in an informative yet down-to-earth and accessible style, this text provides commentary on the basic principles underlying children's development, how to support learning, the basic learning styles and teaching children with special educational needs.
Includes bibliographical references and index.
Keywords: Child development; Child psychology; Teachers' assistants